The inhibitory effect of doxycycline on cisplatin-sensitive and -resistant epithelial ovarian cancer. - Wei Wu; Li-Hua Yu; Bei Ma; Ming-Juan Xu (PLoS ONE)
Background Detecting a new effective and hypotoxic anticancer drug is an emerging new strategy for cancer chemotherapy. Doxycycline (DC) is a kind of antibiotics but also inhibits tumorigenesis. Methods MTT and cell invasion assay, flow cytometry, western-blot analysis and nude mice were used to investigate the effects and underlying mechanisms of doxycycline on epithelial ovarian cancer cells. Results Doxycycline inhibited the proliferation and invasion of SKOV3 and SKOV3/DDP; induced moderate apoptosis of SKOV3/DDP. CXCR4 expression at both mRNA and protein levels was downregulated in both cell lines when treated with doxycycline. Akt and ERK1/2 were involved in doxycycline effect on cell proliferation of SKOV3 but not of SKOV3/DDP. Akt and EKR1/2 phosphorylation were activated by SDF-1α, which was then inhibited by doxycycline in SKOV3. Pro-caspase-3 expression was significantly higher in SKOV3 than that in SKOV3/DDP which was upregulated when treated with doxycycline. In vivo, doxycycline inhibited peritoneal tumor xenograft and decreased malignant ascites. Conclusion Doxycycline not only has an inhibitory effect on ovarian cancer, but also can increase sensitivity to cisplatin. SDF-1α/CXCR4-regulated Akt and ERK 1/2 activations are probably involved in the antitumor effect of doxycycline on SKOV3 cells, while upregulation of pro-caspase-3 may be the main mechanism involved in SKOV3/DDP cells.